Evaluating Assessment Accuracy: Evaluation of the Suitability of Assessment Standards with Early Childhood Development - M., Rembulan Hawnan Wafi; Gulo, Petrus; Suryanigsih, Ni Made Ayu (Universitas Negeri Semarang, 2025)
This study aims to evaluate the assessment standards of Rare Muchtary Kindergarten Denpasar through an evaluation of the suitability of the assessment standards with early childhood development. Using an evaluation research approach, this study seeks to deeply understand the ongoing assessment practices and their relevance to the stages of child development. Data were collected through direct observation in the classroom, in-depth interviews with teachers and principals, and analysis of assessment standard documents and child development records. The results of this study indicate that Rare Muchtary Kindergarten Denpasar is very administratively compliant with the National Assessment Standards, with high scores on objectives, principles, and various assessment techniques (observations, anecdotal notes, conversations, parent reports). However, there is still an opportunity to improve the accuracy and suitability of the assessment implementation with actual child development.